Leaders and Laggards: International Evidence on Spillovers in Returns, Variance, and Trading Volume - Bartosz Gebka (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2006)
This paper investigates the dynamic relationship between index returns, return volatility, and trading volume for eight Asian markets and the US. We find crossborder spillovers in returns to be nonexisting, spillovers in absolute returns between Asia and the US to be strong in both directions, and spillovers in variance to run from Asia to the US. Trading volume, especially on the Asian markets, depends on shocks in domestic and foreign returns as well as on variance, especially those shocks originating in the US. However, only weak evidence is found for trading volume influencing other variables.
Keywords: G15; F36; 330; Financial spillovers; trading volume; Asian crisis